2011
DOI: 10.1007/978-3-642-22212-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Time Data Gathering in Wireless Networks with Omni–Directional Antennas

Abstract: Abstract. We study algorithmic and complexity issues originating from the problem of data gathering in wireless networks. We give an algorithm to construct minimum makespan transmission schedules for data gathering when the communication graph G is a tree network, the interference range is any integer m ≥ 2, and no buffering is allowed at intermediate nodes. In the interesting case in which all nodes in the network have to deliver an arbitrary non-zero number of packets, we provide a closed formula for the mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Optimal protocols have also been designed for trees with d I = 1 in [8]. When no buffering is allowed, the problem has been solved for trees for d I = 1 [5] and for general d I [4] (where a closed-form expression is given when all vertices have exactly one piece of information to transmit). For square grids with the gateway in the centre, a multiplicative 1.5-approximation algorithm is given in [18] and an additive +1 approximation algorithm is given in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal protocols have also been designed for trees with d I = 1 in [8]. When no buffering is allowed, the problem has been solved for trees for d I = 1 [5] and for general d I [4] (where a closed-form expression is given when all vertices have exactly one piece of information to transmit). For square grids with the gateway in the centre, a multiplicative 1.5-approximation algorithm is given in [18] and an additive +1 approximation algorithm is given in [6].…”
Section: Introductionmentioning
confidence: 99%
“…The papers most closely related to our results are [3,4,11,12,15,16]. The data gathering problem is first introduced in [11] under a model for sensor networks similar to the one adopted in this paper.…”
Section: Related Workmentioning
confidence: 95%
“…In [4] (resp. [3]) optimal gathering algorithms for tree networks in the same model considered in the present paper, are given when d I = 1 (resp., d I ≥ 2). In [3] it is also shown that the Gathering Problem is NP-complete if the process must be performed along the edges of a routing tree for d I ≥ 2 (otherwise the complexity is not determined).…”
Section: Related Workmentioning
confidence: 99%